Imagery Analysis In Sing To The Dawn Novel - Yandi Wijaya; Afriana Afriana (LPPM Universitas Putera Batam, 2022)
This research proposed to investigate and identify Imageries analysis in one of literary work, sing to the dawn novel by Minhong Fo as a Singaporean that live and grew up in small village in Thailand. Descriptive qualitative research was the main method which researcher used in this research to analyze kinds of imageries in sing to the dawn novel. There were many imageries expression from the novel that researcher found for the data analysis. The data collected by reading all pages of the novel intensively, carefully and gave more attention for every line of sentences in the novel. For further study and analysis of imageries expressions, it used Laurence Perrine’s theories. There were seven kinds of imageries expression according to Laurence Perrine such as: visual imagery (sense of sight), auditory imagery (sense of sound), tactile imagery (sense of touch), olfactory imagery (sense of smelling), gustatory imagery (sense of taste), organic imagery (sense of internal sensation of human body), and kinesthetic imagery (sense of movement). The result of this research was presented in paragraphs form. From the result, it found some kinds of imageries related to Laurence Perrine’s theories. The most imagery expressions that appeared in this novel was auditory imagery (sense of sound).